Financial Innovation and Economic Growth: Empirical Evidence from Nigeria : Array - Adesete, Ahmed; Auwal Adamu Mohammed; Risikat , Dauda O. (EuroEconomica, 2021)
The study examines the impact of financial innovation on the Nigerian economy using both quarterly and monthly series ranging from 2010 to 2020. Most of the previous studies did not disaggregate the financial innovative channels in Nigeria using a value-based approach and also fail to capture the full data information as they annualized both the quarterly financial innovation data and quarterly GDP time series. The study adopted the autoregressive distributed lag model (ARDL) and the polynomial distributed lag mixed data sampling (PDL MIDAS) model as it is effective when combining low frequency and high-frequency data. The outcome of the ARDL showed that mobile payment platform in Nigeria had a positive significant effect both in the long run and short run while internet web transactions and POS transactions have a negative insignificant effect on the Nigerian economy in the short run and long run. The PDL MIDAS equation result, also confirms mobile payment transactions is positively related to Nigeria’s economic growth while POS transactions were negatively related to the Nigerian economy. The results of the study suggests that financial innovation in the Nigerian financial system has a crucial role to play in the nation’s economy which validates the finance-growth theory. The study, therefore, recommends that there is need to strengthen policies towards improving the performance of the financial innovative channels in Nigeria and improve the financial security of existing payment platforms.